1996
DOI: 10.1056/nejm199603143341104
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for the Treatment of Small Hepatocellular Carcinomas in Patients with Cirrhosis

Abstract: Liver transplantation is an effective treatment for small, unresectable hepatocellular carcinomas in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

100
4,740
19
158

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 6,486 publications
(5,131 citation statements)
references
References 26 publications
100
4,740
19
158
Order By: Relevance
“…[1][2][3] The prioritization of LT recipients with HCC by use of the Model for End-Stage Liver Disease (MELD) allocation system [4][5][6] has resulted in LTs for HCCs now accounting for nearly 25% of all transplants in the United States. 7 Despite continuous refinements in the HCC MELD exception policy, LT recipients with HCC continue to be overprioritized compared with patients with liver failure who do not have cancer, with many studies revealing higher transplant rates despite lower risks of waitlist dropout and inferior survival.…”
mentioning
confidence: 99%
“…[1][2][3] The prioritization of LT recipients with HCC by use of the Model for End-Stage Liver Disease (MELD) allocation system [4][5][6] has resulted in LTs for HCCs now accounting for nearly 25% of all transplants in the United States. 7 Despite continuous refinements in the HCC MELD exception policy, LT recipients with HCC continue to be overprioritized compared with patients with liver failure who do not have cancer, with many studies revealing higher transplant rates despite lower risks of waitlist dropout and inferior survival.…”
mentioning
confidence: 99%
“…Surgery, liver transplantation, or resection is hindered by a high frequency of relapse and cannot be proposed to most patients due to size or local extension of the tumor at the time of diagnosis. [5][6][7][8][9][10][11] For these patients, intraarterial chemoembolization or percutaneous ethanol injection have been proposed but have failed to show any survival benefit. 9,12,13 Therefore, it is of importance to develop new therapeutic approaches such as gene transfer strategies.…”
mentioning
confidence: 99%
“…21 In 1993, Bismuth et al 22 reported that patients with fewer than 3 tumor nodules (each < 3 cm in diameter) were suitable candidates for liver transplantation because their disease-free survival rate after the procedure was superior to the rate after liver resection. Consequently, the performance of liver transplantation for patients with small HCCs became established after the 1996 publication of a study by Mazzaferro et al 23 They reported excellent outcomes after liver transplantation for patients with a solitary HCC nodule less than 5 cm in diameter or with up to 3 HCC nodules that were each less than 3 cm in diameter; these features were designated the Milan criteria. The 5-year survival rate of patients with HCC selected according to the Milan criteria currently exceeds 70%.…”
Section: History Of Liver Transplantation For Hccmentioning
confidence: 99%